2014
DOI: 10.1002/pc.23163
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of poly(ε‐caprolactone) solutions containing graphene oxide: Effects of graphene oxide content and oxidation level

Abstract: The morphological appearance, fiber diameter, and structure of poly(e-caprolactone) (PCL) nanofibers produced by the electrospinning process were studied in the presence of different amounts of graphene oxide (GO) with different oxidation levels. Scanning electron microscope micrographs of electrospun fibers showed that the average fiber diameter decreases in the presence of GO with different loading and oxidation levels. The loading level of GO especially higher than 0.3 wt% was influential in decreasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Graphene oxide Poly (vinyl acetate) (PVAc) [56] Graphene oxide Polycaprolactone (PCL) [42,56] Functionalized graphene oxide Poly (lactic acid) (PLA) [26,41] Graphene oxide poly(lactic-co-glycolic acid) (PLGA) and collagen (Col) [40] Graphene oxide poly(lactic-co-glycolic acid) (PLGA) [32,40] Graphene oxide PLA and polyurethane (PU) [38] Graphene oxide Polyurethane (PU) [38,53,55] Graphene oxide Polyethylene oxide (PEO)/chitosan (CS) [44] Graphene oxide Poly (vinyl alcohol) (PVA) [31,35,44,48] Reduced graphene oxide Poly (vinyl alcohol) (PVA) [24,27] Graphene oxide PVA and chitosan CS [33,47] Graphene oxide Nylon 6-6 [52] Reduced graphene oxide Nylon-6 [57] Graphene oxide Nylon-6 [34] Reduced graphene oxide Poly(carbonate urethane) (PCU) [30] Reduced graphene oxide polyvinyl pyrrolidone (PVP) [25] Reduced graphene oxide polyacrylonitrile (PAN) [25,29,36] Functionalized graphene oxide polyacrylonitrile (PAN) [28] Graphene oxide Polyacrylonitrile (PAN) [28,50] Reduced graphene oxide Polyvinyl Butyral (PVB) [46] Graphene oxide Polyacrylic acid (PAA) [54] Table 2. Reported literatures on electrospun GO.…”
Section: Graphene Oxide Polymer Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene oxide Poly (vinyl acetate) (PVAc) [56] Graphene oxide Polycaprolactone (PCL) [42,56] Functionalized graphene oxide Poly (lactic acid) (PLA) [26,41] Graphene oxide poly(lactic-co-glycolic acid) (PLGA) and collagen (Col) [40] Graphene oxide poly(lactic-co-glycolic acid) (PLGA) [32,40] Graphene oxide PLA and polyurethane (PU) [38] Graphene oxide Polyurethane (PU) [38,53,55] Graphene oxide Polyethylene oxide (PEO)/chitosan (CS) [44] Graphene oxide Poly (vinyl alcohol) (PVA) [31,35,44,48] Reduced graphene oxide Poly (vinyl alcohol) (PVA) [24,27] Graphene oxide PVA and chitosan CS [33,47] Graphene oxide Nylon 6-6 [52] Reduced graphene oxide Nylon-6 [57] Graphene oxide Nylon-6 [34] Reduced graphene oxide Poly(carbonate urethane) (PCU) [30] Reduced graphene oxide polyvinyl pyrrolidone (PVP) [25] Reduced graphene oxide polyacrylonitrile (PAN) [25,29,36] Functionalized graphene oxide polyacrylonitrile (PAN) [28] Graphene oxide Polyacrylonitrile (PAN) [28,50] Reduced graphene oxide Polyvinyl Butyral (PVB) [46] Graphene oxide Polyacrylic acid (PAA) [54] Table 2. Reported literatures on electrospun GO.…”
Section: Graphene Oxide Polymer Referencesmentioning
confidence: 99%
“…The effect of GO loading into PCL was investigated in presence of different oxidation levels [26]. GO dispersibility, wettability, polarity and charge relaxation time, which assess the fibre diameter, increase with oxidation level.…”
Section: Advances In Carbon Nanostructuresmentioning
confidence: 99%
“…However there are few studies on the mechanical properties of electrospun PCL fibers in the presence of different amounts of GO and RGO. In our own last work we studied the effect of oxidation and loading levels of GO in the process of PCL electrospinning on electrospun fiber diameter and morphology [19]. In addition, Wan et al [20] have only shown that the tensile strength and Young's modulus of fibrous membrane increase 95% and 66% respectively at the presence of 0.3 wt.% GO due to the reinforcing effect of GO on PCL nanofibers.…”
Section: Introductionmentioning
confidence: 98%
“…It can be observed that the mean diameter of the nanofiber is 1459, 1923, and 2543 nm, respectively. The results show a continuous increase in the diameter of the nanofibers with the increase of GO concentration . EDS mapping data are presented in Table for three samples.…”
Section: Resultsmentioning
confidence: 90%
“…The results show a continuous increase in the diameter of the nanofibers with the increase of GO concentration. 43,44 EDS mapping data are presented in Table II for three samples. An obvious change cannot be observed for the three samples as the amount of GO is low.…”
Section: Resultsmentioning
confidence: 99%